A micro-computed tomographic study using a novel test model to assess the filling ability and volumetric changes of bioceramic root repair materials - Esteves Torres, Fernanda Ferrari [UNESP]; Pinto, Jader Camilo [UNESP]; Figueira, Gabriella Oliveira [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Korean Acad Conservative Dentistry, 2021)
Objectives: New premixed bioceramic root repair materials require moisture for setting. Using micro-computed tomography (micro-CT), this study evaluated the filling ability and volumetric changes of calcium silicate-based repair materials (mineral trioxide aggregate repair high-plasticity [MTA HP] and Bio- C Repair, Angelus), in comparison with a zinc oxide and eugenol-based material (intermediate restorative material [IRM]; Dentsply DeTrey). Materials and Methods: Gypsum models with cavities 3 mm deep and 1 mm in diameter were manufactured and scanned using micro-CT (SkyScan 1272. Bruker). The cavities were filled with the cements and scanned again to evaluate their filling capacity. Another scan was performed after immersing the samples in distilled water for 7 days to assess the volumetric changes of the cements. The statistical significance of differences in the data was evaluated using analysis of variance and the Tukey test with a 5% significance level. Results: Bio- C Repair had a greater filling ability than MTA HP (p < 0.05). IRM was similar to Bio-C and MTA HP (p > 0.05). MTA HP presented the largest volumetric change (p < 0.05), showing more volume loss than Bio-C and IRM, which were similar (p > 0.05). Conclusions: Bio-C Repair is a new endodontic material with excellent filling capacity and low volumetric change. The gypsum model proposed for evaluating filling ability and volumetric changes by micro- CT had appropriate and reproducible results. This model may enhance the physicochemical evaluation of premixed bioceramic materials, which need moisture for setting.
Keywords: Biocompatible materials; Endodontics; Methods; X-ray microtomography